Technomobility in China Young Migrant Women and Mobile Phones. - Wallis, Cara. (New York : NYU Press, 2013)
As unprecedented waves of young, rural women journey to cities in China, not only to work, but also to "see the world"and gain some autonomy, they regularly face significant institutional obstacles as well as deep-seated anti-rural prejudices. Based on immersive fieldwork, Cara Wallis provides an intimate portrait of the social, cultural, and economic implications of mobile communication for a group of young women engaged in unskilled service work in Beijing, where they live and work for indefinite periods of time. While simultaneously situating her work within the fields of feminist studies.
RS; T; U; W; X; Y; Z; About the Author.
Description based on print version record.
Keywords: Migration, Internal -- China -- History -- 21st century; Technology and women -- China; Women -- China -- Social conditions -- 21st century; Women -- Social networks -- China; Women -- China -- Social conditions -- 21st century; Migration, Internal -- China -- History -- 21st century; Technology and women -- China; COMPUTERS / Information Technology; SOCIAL SCIENCE / Women's Studies; Electronic books